Analisis Kepuasan Pelayanan PT. SAK Dengan Metode Uji Validitas dan Reliabilitas - Rizky Fatmawati Pudjo Wita; Minto Waluyo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study is motivated by service quality which is one of the most influential aspects in the success of a business. PT. SAC as a service provider company is required to always pay attention to service user satisfaction with the services provided. This research is quantitative research. Data collection was obtained from primary data from the results of questionnaires with questions that had been asked by service users via Google Form. Questionnaires were given to 30 service users randomly. Data was collected during the MBKM internship at PT. SAC for 5 months, starting on 1 August 2023 – 31 December 2023. Data processing was carried out using validity and reliability tests. Data processing was carried out using the SPSS application to find solutions to the above problems. Valid, namely that data processing must be carried out properly and correctly. The results of the reliability test calculations show that all r calculations for each question, namely, R1 to R9, show a value greater than the r table, namely 0.361, so by using a significance level (α) of 5%, the questionnaire studied is valid. The Cronbach Alpha value shows 0.742, which means it is greater than the r table, namely 0.361 with the Cronbach Alpha value.